THE CORRELATION BETWEEN ANXIETY IN SPEAKING PERFORMANCE IN SEKOLAH MENENGAH ATAS NEGERI 1 MENGWI - Putu Nada Dita Pratama; I Wayan Suarnajaya; I Nyoman Pasek Hadi Saputra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This research investigated the anxiety and speaking performance of students in the second grade of SMA Negeri 1 Mengwi. The objectives of this research was to determine relationship between anxiety and speaking performance. This research is a correlational study, and this study was designed using a quantitative method. The samples were 106 students of SMA Negeri 1 Mengwi in the 2020/2021 academic year. The data were collected using a questionnaire and speaking rubric. The result of this research revealed a significant correlation between the anxiety of students and their speaking performance. The strength of the relationship was highly negative, which indicated that if the anxiety of the students was high, the speaking performance would be poor.